2013
DOI: 10.26719/2013.19.7.589
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C virus infections and their related risk factors in Libya: a national seroepidemiological survey

Abstract: A high prevalence of hepatitis B (HBV) and C virus (HCV) infections has been reported among specific patient groups in Libya; a survey was thus designed to determine the extent of the problem at the national level. A multistage sampling design covering all administrative areas of Libya was applied, covering > 65 000 individuals of all age groups. All subjects gave a blood sample and completed a questionnaire on demographic and risk behaviour data. The prevalence of HBV surface antigen (HBsAg) and anti-HCV were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 30 publications
8
22
1
Order By: Relevance
“…The strengths of the present study include the fact that it involved multiple centers, which allowed us to identify the seroprevalence of HBV and HCV, the working period, and the different occupational risks of acquiring infection in HCWs in five different sites in eastern Libya. The lower prevalence of HBsAg (1.8%) was similar to data from a national population-based sero-epidemiological survey that found that the overall prevalence of HBV was 2.2% [6]. Two previous local studies carried out in Libya have found that 31% and 14.8% of HCWs in Tripoli and Benghazi, respectively, were infected [15,16], and the low prevalence among HCWs in the present study might be explained by their awareness of the routes of HBV transmission, the implementation of infection control measures and a free vaccination program.…”
Section: Occupationsupporting
confidence: 85%
See 1 more Smart Citation
“…The strengths of the present study include the fact that it involved multiple centers, which allowed us to identify the seroprevalence of HBV and HCV, the working period, and the different occupational risks of acquiring infection in HCWs in five different sites in eastern Libya. The lower prevalence of HBsAg (1.8%) was similar to data from a national population-based sero-epidemiological survey that found that the overall prevalence of HBV was 2.2% [6]. Two previous local studies carried out in Libya have found that 31% and 14.8% of HCWs in Tripoli and Benghazi, respectively, were infected [15,16], and the low prevalence among HCWs in the present study might be explained by their awareness of the routes of HBV transmission, the implementation of infection control measures and a free vaccination program.…”
Section: Occupationsupporting
confidence: 85%
“…A majority of countries in the Middle East show an intermediate or high endemicity of HBV infection, which clearly poses a serious public health problem in the region [5]. The prevalence of HBV and HCV in Libya has been recently reported in a large general population-based study to be 2.2% for HBsAg and 1.8% for Anti-HCV antibodies [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, 24% of donors didn't have either B hepatitis or C hepatitis. Elzouki has found among the blood donors of Libya a prevalence of the antigen of the hepatitis B and anti-hepatitis C antibodies respectively of 2.2% and 1.3% [9]. Patients with immunosuppressive status with respect to the hepatitis C virus have been met [10].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were found to be comparable with that of 76.2%:23.4% of Rajesh N Gacche et al 14 and 72.4%:27.6% of A.N.Elzouki et al study group. 15 …”
Section: Literacymentioning
confidence: 99%